Revisualizing Italian Silentscapes 1896-1922 (RevIS): i paesaggi italiani del primo cinema nelle scuole secondarie di II grado - Piva, Manlio Celso; Guarneri, Michael (Aesthetica Preprint, 2024)
The essay describes the preliminary findings of the 2022-2025 research project Revisualizing Italian Silentscapes 1896-1922. Landscapes and Locations of the Early Italian Cinema One Hundred Years Later. This project has two aims: first, it studies how the films produced from 1896 to 1922 made use of Italy’s landscapes to represent the nation and its various territories; second, it promotes the knowledge, the reappropriation and the reuse of the largely neglected silent cinema heritage in all areas of present-day society, starting from public schools. The essay discusses the planning, the testing and the results of the learning activities conducted at four high schools in Lombardia and Veneto throughout 2023 and 2024. As part of these learning activities, the students explore the streets of their hometowns and revisualize by means of photos and videos the very same Italian locations featured in late-nineteenth-century and early-twentieth-century cinema; then, the students return to class and create open-access online maps highlighting the similarities and differences between past and present. By rediscovering cinematic landscapes from the silent era, the students gain a new understanding of their everyday environment and make their discoveries publicly accessible to strengthen their own – and their local community’s – ties to the territory and sense of belonging to it.